Musyawarah Sebagai Prinsip Politik Islam Dalam Pengambilan Keputusan - Nur Afrija Putri; Zurah Aisyiah Sifa; Anggina Rizky Fadla Wardani; Nurhalima Rambe; Ummi fahrizka piliang (Albayan Journal of Islam and Muslim Societies, 2025)
Musyawarah (consultation) constitutes one of the fundamental principles of governance in Islamic political thought and serves as an essential mechanism for realizing justice, participation, and collective responsibility in public affairs. This study aims to examine the concept of musyawarah from the perspective of Islamic constitutional law, including its normative foundations, historical development, and relevance within contemporary political systems. The research employs a normative legal method using conceptual, historical, and doctrinal approaches. Primary sources consist of Qur’anic verses, prophetic traditions, and classical Islamic political thought, while secondary sources include scholarly literature on Islamic constitutional law and political theory. The findings demonstrate that musyawarah is not merely a procedural mechanism for decision-making but also represents an ethical and constitutional principle rooted in the values of equality, justice, accountability, and public participation. Historically, the practice of musyawarah was prominently implemented during the era of the Rightly Guided Caliphs (Khulafā’ al-Rāshidūn), reflecting a governance model based on collective deliberation and public consultation. Furthermore, the study reveals that although musyawarah and modern democracy originate from different philosophical foundations, both share common principles concerning participation, representation, and accountability in governance. In the Indonesian context, musyawarah possesses strategic significance as a bridge between Islamic political values and the constitutional principles embodied in Pancasila and democratic governance. Therefore, revitalizing musyawarah within contemporary political institutions can contribute to strengthening democratic quality, promoting inclusive decision-making, and fostering good governance in Muslim-majority societies.